Designing preschool interventions : a practitioner's guide - Barnett, David W. (Guilford, 1999)
Critical issues in preschool interventions Consulting with parents and teachers Principles and techniques for observing Designing effective interventions Evaluating intervention design and outcomes Developing new behaviors and modifying existing behaviors Managing severe problem behaviors Changing roles within family systems Parent interventions for severe and risk-related problem behaviors The classroom as ecosystem Classroom social and safety-related interventions